Electron Acceptors With a Truxene Core and Perylene Diimide Branches for Organic Solar Cells: The Effect of Ring-Fusion - Lin, Kaiwen; Wang, Shiliang; Wang, Zhenfeng; Yin, Qingwu; Liu, Xi; Jia, Jianchao; Jia, Xiao'e; Luo, Peng; Jiang, Xiaofang; Duan, Chunhui; Huang, Fei; Cao, Yong (Frontiers in Chemistry, 2018)
In this work, a star-shaped planar acceptor named FTr-3PDI was synthesized via ring-fusion between truxene core and three bay-linked perylene diimide (PDI) branches. Compared to the unfused non-planar acceptor Tr-3PDI, FTr-3PDI exhibits better structural rigidity and planarity, as well as more effective conjugation between truxene core and PDI branches. As a result, FTr-3PDI shows up-shifted energy levels, enhanced light absorption coefficient, increased electron mobility, and more favorable phase separation morphology in bulk-heterojunction (BHJ) blend films as compared to Tr-3PDI. Consequently, FTr-3PDI afforded higher power conversion efficiency (PCE) in BHJ solar cells when blended with a polymer donor PTB7-Th. This work demonstrates that ring-fusion is a promising molecular design strategy to combine the merits of truxene and PDI for non-fullerene acceptors used in organic solar cells.